THE PRINCIPAL'S ROLE IN DEVELOPING SCHOOL CULTURE AT SMA NEGERI 5 KUPANG - Novia Andini Sarifudin Ahmad (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2022)
The objective of this research was to determine the role of the principal in developing school culture and to identify factors that support and inhibit the principal's role in developing school culture at SMA Negeri 5 Kupang. The qualitative method was implemented in this research, where the principal, teachers, and students from SMA Negeri 5 Kupang become subjects of research through a purposive sampling technique. Furthermore, data collection techniques include observation, interviews, and documentation. After that, the data analysis implements data collection, data reduction, data display, and conclusion. Based on research conducted at SMA Negeri 5 Kupang, there are two roles of the school (1) implementing regulations that can build school culture, such as discipline, tolerance, honesty, responsibility, overcoming problems, and giving firmness fairly to all school members, and (2) build communication in order to establish a good cooperative relationship with all school members. Besides, in the development of school culture, there are both supportive and inhibiting factors. School regulations and school community participation are important factors in developing school culture. While the lack of school community cohesion is an impediment to developing school culture.